2013
DOI: 10.4238/2013.january.30.5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chicken natural resistance-associated macrophage protein encoding genes (Nramp1 and Nramp2) and association with salmonellosis resistance

Abstract: ABSTRACT. Natural resistance-associated macrophage protein 1 and 2 encoding genes (Nramp1 and Nramp2) are related to many diseases. We cloned the cDNA of chicken Nramp1 and Nramp2 genes, characterized their expression and polymorphisms, and investigated the association of some SNPs with resistance to salmonellosis. The Nramp1 cDNA was 1746 bp long and the Nramp2 cDNA was 1938 bp long. These cDNAs are similar to previously reported cDNAs, varying by two and one amino acids, respectively. The chicken Nramp1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
(37 reference statements)
1
13
1
2
Order By: Relevance
“…The levels of NRAMP1 expressed in liver, spleen and lymphoid were higher, comparatively, while the levels in brain and kidney were lower. NRAMP1 gene expression has been observed by RT-PCR in different tissues from chickens where higher expression levels were found in liver, spleen, thymus and much lower expression levels in brain, kidney, which is consistent with our results in pigs (He et al, 2013). …”
Section: Resultssupporting
confidence: 92%
“…The levels of NRAMP1 expressed in liver, spleen and lymphoid were higher, comparatively, while the levels in brain and kidney were lower. NRAMP1 gene expression has been observed by RT-PCR in different tissues from chickens where higher expression levels were found in liver, spleen, thymus and much lower expression levels in brain, kidney, which is consistent with our results in pigs (He et al, 2013). …”
Section: Resultssupporting
confidence: 92%
“…The chicken SCL11A1 gene was previously shown to be expressed in liver, thymus and spleen. As in mice, SCL11A1 polymorphism was associated with resistance to Salmonellosis (57). Consistent with that report, SLC11A1 was undetectable in bursal cell populations (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…It serves an apparent role in host defense against microbial infection (Blackwell, 1996;Govoni and Gros, 1998;He et al, 2013), and is considered an important immune response-related gene (Wu et al, 2008;Chen et al, 2012;Badawy et al, 2013). Previous studies have indicated that the Nramp1 protein serves a role in pathogenic infection resistance via a mechanism involving the transport of metal ions such as Mn 2+ and Fe…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study found that the Nramp1 gene could influence Bacillus CalmetteGuérin (BCG) tuberculosis vaccine efficacy, indicating that Nramp1 plays an important immune regulation function with regard to pathogenic response (Badawy et al, 2013). Similarly, He et al (2013) found that A24101991G of Nramp1 was significantly associated with salmonellosis resistance.…”
Section: Introductionmentioning
confidence: 94%